Xylem anatomical responses of Larix Gmelinii and Pinus Sylvestris influenced by the climate of Daxing’an mountains in Northeastern China - Farooq, Taimoor Hassan; Yasmeen, Sumaira; Shakoor, Awais; Nawaz, Muhammad Farrakh; Rashid, Muhammad Haroon U.; Ahmad, Sarir; Rasheed, Majeeda; Li, He; Li, Qian (Frontiers in Plant Science, 2023)
Wood anatomy and plant hydraulics play a significant role in understanding species-specific responses and their ability to manage rapid environmental changes. This study used the dendro-anatomical approach to assess the anatomical characteristics and their relation to local climate variability in the boreal coniferous tree species Larix gmelinii (Dahurian larch) and Pinus sylvestris var. mongolica (Scots pine) at an altitude range of 660 m to 842 m. We measured the xylem anatomical traits (lumen area (LA), cell wall thickness (CWt), cell counts per ring (CN), ring width (RW), and cell sizes in rings) of both species at four different sites Mangui (MG), Wuerqihan (WEQH), Moredagha (MEDG) and Alihe (ALH) and investigated their relationship with temperature and precipitation of those sites along a latitude gradient. Results showed that all chronologies have strong summer temperature correlations. LA extremes were mostly associated with climatic variation than CWt and RWt. MEDG site species showed an inverse correlation in different growing seasons. The correlation coefficient with temperature indicated significant variations in the May-September months at MG, WEQH, and ALH sites. These results suggest that climatic seasonality changes in the selected sites positively affect hydraulic efficiency (increase in the diameter of the earlywood cells) and the width of the latewood produced in P. sylvestris. In contrast, L. gmelinii showed the opposite response to warm temperatures. It is concluded that xylem anatomical responses of L. gmelinii and P. sylvestris showed varied responses to different climatic factors at different sites. These differences between the two species responses to climate are due to the change of site condition on a large spatial and temporal scale.